Effects of curvature radius on flexible eddy current array sensors for the curved surface of metal components - Deng, Zhiyang; Li, Danyu; Qi, Pan; Shao, Wenbin; Chen, Tao; Song, Xiaochun; Kang, Yihua (Frontiers in Physics, 2022)
The flexible eddy current array sensor owns the advantages of high sensitivity and strong adaptability, but the results are always affected by the curvature radius of complex curved surfaces. The relationship between the curvature radius of the curved surface and detection signals for surface-breaking cracks is mainly discussed. The change of magnetic field caused by the curved surface in the present eddy current testing is specially pointed out, which manifest themselves in the compression or enhancement of the testing signal in its peak value and the baseline drifts. Simulation and experimental results indicate that the concave surface weakens the signal, while the convex surface enhances the signal. The signal amplitude decreases with the decrease in the curvature radius for the concave surface, while it is the opposite for the convex surface. Meanwhile, coil spacing significantly affects the amplitude–curvature radius curve. Furthermore, the fluctuation characteristic affected by the curvature radius under different coil spacing is analyzed. The discovery and results will benefit the quantitative evaluation of flexible eddy current array testing.